PENGEMBANGAN BAHAN AJAR E- LEARNING BERBASIS MODEL KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI SISWA KELAS VII SMP NEGERI 3 TARUTUNG - Sitompul, Fatimah; Hasratuddin, Hasratuddin; Sri Ardiasih, Lidwina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the improvement of students' descriptive text writing skills using contextual model-based e-learning teaching materials, find contextual model-based e-learning teaching materials that are practical in improving students' descriptive text writing skills, and find contextual model-based e-learning teaching materials that effective for improving the descriptive text of the seventh grade students of SMP Negeri 3 Tarutung's. The research population was all seventh grade students of SMP Negeri 3 Tarutung. The sample is set at 60 students. The research instrument consisted of expert assessment sheets and student learning outcomes tests. The analysis technique uses expert validation and calculates Gain and N-gain with student test results. The results showed that there was an increase in the ability to write descriptive texts of students using e-learning teaching materials based on contextual models developed in class VII of SMPN 3 Tarutung as evidenced by the average acquisition of 38.67 pretest results increasing to 85.42. E-learning teaching materials based on contextual models were developed practically in improving students' description writing skills in class VII SMP Negeri 3 Tarutung, North Tapanuli Regency. The e-learning teaching materials based on the contextual model that were developed were effectively used to improve students' description writing skills in grade VII SMP Negeri 3 Tarutung, North Tapanuli Regency. The calculation result or N-Gain value is 0.71 with good learning improvement result category.